Stock Price Manipulation (Pump and Dump Stock) and Threats to Indonesian Capital Market Classification: A Legal Analysis from an Investor Protection Perspective - Gneissa Beltsazar; Lastuti Abubakar; Tri Handayani (Indonesian Journal Publisher, 2026)
This study aims to juridically analyze the practice of stock price manipulation (“gorengan stocks”) as a form of market abuse from the perspective of investor protection and the maintenance of capital market integrity in Indonesia. The background of this research is based on the increasing prevalence of pump and dump practices, which result in stock prices that do not reflect the fundamental conditions of the issuing companies. This phenomenon potentially harms investors, particularly retail investors, and undermines trust in the capital market. This research employs a normative juridical method, utilizing both a statutory approach and a conceptual approach, supported by primary, secondary, and tertiary legal materials. The findings indicate that the practice of gorengan stocks constitutes a form of market manipulation that is explicitly prohibited under Law Number 8 of 1995 concerning Capital Markets, particularly in Articles 90 to 93. In this context, the Financial Services Authority (OJK) plays a crucial role in supervision and law enforcement, while the Indonesia Stock Exchange (IDX) is responsible for maintaining orderliness and transparency in securities trading. However, the effectiveness of supervision and law enforcement continues to face significant challenges, particularly due to the increasingly complex modes of manipulation, including those conducted through social media and the use of nominee accounts. In addition to causing financial losses to investors, such practices also contribute to declining market confidence and may negatively affect the global perception of the quality of Indonesia’s capital market. Therefore, strengthening regulatory frameworks, enhancing supervisory mechanisms, and promoting continuous investor education are essential to establish a transparent, fair, and trustworthy capital market. This study is expected to contribute to the development of capital market legal policies as well as investor protection in Indonesia.